The Influence of Visitor Motivation on Visiting Decisions (Case Study on Tourism Visitors to Kampoeng Taipa Sorowako Nuha Sub-District East Luwu District) - Malviansyah, Zakwan; Rivai, Andi Muhammad; Akib, Haedar (Universitas Negeri Makassar, 2025)
This study examines the influence of visitor motivation on visiting decisions. The purpose of this study was to determine the level of motivation of visitors to Kampoeng Taipa tourism, to determine the level of decision to visit Kampoeng Taipa tourism, and to determine the influence of visitor motivation on the decision to visit Kampoeng Taipa tourism. The research approach is quantitative. This research was conducted in Kampoeng Taipa Sorowako, Nuha District, East Luwu Regency. The data sources in this study were visitors to Kampoeng Taipa tours from January to June 2022. Data collection techniques were in the form of observation, question naires, and documentation. Data analysis techniques include normality test, descriptive analysis, simple linear regression analysis, analysis of the coefficient of determination. The results of the study show that the indicator used for each of these variables indicate the variable of visitor motivation in the good category. The indicators on the visiting decision variable are in the very good category. Based on the correlation test, there is a high relationship between the two variable. It can be concluded that there is a significant influence between visitor motivation and the decision to visit tourist visitors to Kampoeng Taipa Sorowako, Nuha District, East Luwu Regency.Keywords: Visitor Motivation, Visiting Decision